2016
DOI: 10.1002/jor.23402
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of bone in the femoral head treated with ibandronate and BMP-2 following ischemic osteonecrosis

Abstract: Bone morphogenetic protein (BMP)-2 and ibandronate (IB) decrease the femoral head deformity following ischemic osteonecrosis of the femoral head (ONFH). The purpose of this study was to determine the effects of BMP-2 and IB on the mineral content and nanoindentation properties of the bone following ONFH. ONFH was surgically induced in the femoral head of piglets. There were five groups: normal control, untreated, IB, BMP, and BMP + IB (n = 5/group). Backscattered electron imaging, Raman spectroscopy, and nanoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…A total of 49 full-text articles were assessed for eligibility, but 26 were excluded for different reasons (10 review articles, eight studies lacked a control group, and data for eight studies were unavailable). The remaining 23 articles including 16 animal studies 16 19 , 26 – 37 and seven human studies 14 , 15 , 20 , 21 , 38 – 40 were passed for synthetic evaluation for this meta-analysis. A summary of selected studies is shown in Table 1 , while the basic techniques of the included studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 49 full-text articles were assessed for eligibility, but 26 were excluded for different reasons (10 review articles, eight studies lacked a control group, and data for eight studies were unavailable). The remaining 23 articles including 16 animal studies 16 19 , 26 – 37 and seven human studies 14 , 15 , 20 , 21 , 38 – 40 were passed for synthetic evaluation for this meta-analysis. A summary of selected studies is shown in Table 1 , while the basic techniques of the included studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the animal studies of Aruwajoye OO, et al . 19 and Zou Y, et al . 18 showed that the use of ibandronate alone did not obviously improve osteonecrosis, while the combination of ibandronate and other drugs such as BMP-2 or simvastatin could exert better protective effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the benefits of BMP-2 on arthritis have been previously investigated ( 21 ), the underlying mechanism of the rBMP-2/Fc-mediated signaling pathway for osteonecrosis of the femoral head in a mouse model remains unknown. It was observed that the expression of BMP-2 was positively associated with the gene signatures of NF-κB signaling, indicating that the NF-κB signaling pathway may be regulated by BMP-2 in bone synovial cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) belong to the transforming growth factor-β superfamily that regulates a number of cellular activities ( 20 ). Previous studies have demonstrated that BMPs serve important roles in different forms of arthritis and their disease activity ( 21 23 ). Grcevic et al ( 24 ) previously reported that the peripheral blood expression profiles of BMPs may act as predictive markers for the development of arthritis, its disease activity, therapeutic responsiveness and overall prognosis.…”
Section: Introductionmentioning
confidence: 99%